Impacts of parameterized orographic drag on the Northern Hemisphere winter circulation. (5th February 2016) - Sandu, Irina; Bechtold, Peter; Beljaars, Anton; Bozzo, Alessio; Pithan, Felix; Shepherd, Theodore G.; Zadra, Ayrton
Abstract: A recent intercomparison exercise proposed by the Working Group for Numerical Experimentation (WGNE) revealed that the parameterized, or unresolved, surface stress in weather forecast models is highly model‐dependent, especially over orography. Models of comparable resolution differ over land by as much as 20% in zonal mean total subgrid surface stress ( τtot ). The way τtot is partitioned between the different parameterizations is also model‐dependent. In this study, we simulated in a particular model an increase in τtot comparable with the spread found in the WGNE intercomparison. This increase was simulated in two ways, namely by increasing independently the contributions to τtot of the turbulent orographic form drag scheme (TOFD) and of the orographic low‐level blocking scheme (BLOCK). Increasing the parameterized orographic drag leads to significant changes in surface pressure, zonal wind and temperature in the Northern Hemisphere during winter both in 10 day weather forecasts and in seasonal integrations. However, the magnitude of these changes in circulation strongly depends on which scheme is modified. In 10 day forecasts, stronger changes are found when the TOFD stress is increased, while on seasonal time scales the effects are of comparable magnitude, although different in detail. At these time scales, the BLOCK scheme affects the lower stratosphere winds through changes in the resolved planetary waves which are associated with surface impacts, while the TOFD effects are mostly limited to the lower troposphere. The partitioning of τtot between the two schemes appears to play an important role at all time scales. Key Points: Parameterized orographic drag affects the Northern Hemisphere winter circulation at all time scales The partition of the surface stress between various parameterizations affects circulation aspects